2016
DOI: 10.1002/jbmr.2867
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Trabecular Bone Score and Lumbar Spine Volumetric BMD Is Attenuated Among Older Men With High Body Mass Index

Abstract: Trabecular bone score (TBS) has been proposed as a dual-energy X-ray absorptiometry (DXA) derived measure of underlying quality of trabecular bone; however, TBS is not considered valid for those with body mass index (BMI) >37 kg/m2. Our objective was to determine the association between TBS and lumbar spine (trabecular) volumetric BMD (LS-VBMD) and to examine whether the association varied by BMI and body composition among older men below this clinical threshold. We used regression models to study 3479 men age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
21
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 23 publications
5
21
0
1
Order By: Relevance
“…We observed that the association between TBS and clinical vertebral fracture varied by BMI, being attenuated among those with higher BMI. This is consistent with the hypothesis that a larger thickness of soft tissue in front of and behind the lumbar spine may introduce more TBS measurement error and supported by our previous finding that the association of TBS with volumetric trabecular BMD measured with lumbar spine QCT becomes weaker as BMI increases …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We observed that the association between TBS and clinical vertebral fracture varied by BMI, being attenuated among those with higher BMI. This is consistent with the hypothesis that a larger thickness of soft tissue in front of and behind the lumbar spine may introduce more TBS measurement error and supported by our previous finding that the association of TBS with volumetric trabecular BMD measured with lumbar spine QCT becomes weaker as BMI increases …”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with the hypothesis that a larger thickness of soft tissue in front of and behind the lumbar spine may introduce more TBS measurement error (10) and supported by our previous finding that the association of TBS with volumetric trabecular BMD measured with lumbar spine QCT becomes weaker as BMI increases. (4) In general, our results from MrOS are consistent with findings from the Manitoba Bone Density database as TBS in the latter study was not associated with incident clinical vertebral fractures in men after adjustment for lumbar spine BMD. In contrast, TBS has been shown to be associated with incident clinical vertebral fractures among women in the Manitoba cohort (11) and with incident radiographic vertebral fractures among women in the OPUS (12) and JPOS (13) studies, adjusted for both age and lumbar spine BMD.…”
Section: Discussionsupporting
confidence: 88%
“…The rationale behind these findings was that a higher skeleton load may cause an adaptive response of the bone, which may eventually result in better and stronger bones. We found, as reported previously, a negative association of TBS v3.03 with the body composition parameters . This paradoxical correlation has been explained with the possible artifactual effect that the regional presence of the soft tissue might have on the DXA scan.…”
Section: Discussionsupporting
confidence: 79%
“…We found, as reported previously, a negative association of TBS v3.03 with the body composition parameters. (12)(13)(14)(15)(16) This paradoxical correlation has been explained with the possible artifactual effect that the regional presence of the soft tissue might have on the DXA scan. Apparently, accounting for the BMI in the computational algorithm of TBS v3.03 could not completely overcome this technical issue; whereas the updated algorithm which accounts for the regional soft tissue thickness seems to deal with it.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation